Assessing the impact of the four COVID-19 variants and the vaccine coverage on mortality in Malta over 2 years: An observational case study - Cuschieri, Sarah; Grech, Stephan; Grech, Victor (Frontiers in Public Health, 2022)
Background Mortality may quantify a population's disease burden. Malta, like other European countries, experienced COVID-19 surges in cases and mortality across the pandemic. This study assesses COVID-19's mortality impact, while exploring the effects of the four dominant COVID-19 variants and that of the vaccination coverage on the Maltese population. Methods COVID-19 data (cases, mortality, positivity, and vaccination rates) was obtained from the websites of the European Center for Disease Prevention and Control and the Malta Ministry of Health. Data was categorized into the four periods according to reported dominant COVID-19 variant. Years of life lost (YLL) and Case-Fatality-Ratio (CFR) for each period were estimated. CFR was also estimated for the pre-vaccine and post-vaccine periods. Results The original COVID-19 period (36 weeks) had the highest YLL (4,484), followed by the Omicron variant period (12 weeks; 1,398). The Alpha variant period (7 weeks) had the highest CFR (1.89%) followed by the Original COVID-19 (1.35%). The pre-vaccine (1.59%) period had higher CFR than the post-vaccine period (0.67%). Conclusion Various factors contributed to mortality, but the variant's infectivity, transmissibility, and the effectiveness of the vaccine against the variant play an important role. Reducing mortality by embracing mass vaccination that targets current variants along with other non-pharmaceutical interventions remains paramount.